(untitled) (Advances in Law, Pedagogy, and Multidisciplinary Humanities, 2026)
This paper examines the systematic siege warfare tactics employed in the 2023-2024 Gaza conflict as a critical case study in the weaponization of humanitarian access and the erosion of the foundational International Humanitarian Law (IHL) principle of distinction. Moving beyond the limited legal debate surrounding sieges per se, the analysis contends that the comprehensive closure of Gaza, characterized by the sustained, near-total blockade of food, water, fuel, medicine, and humanitarian personnel, represents a deliberate strategic recalibration. This strategy instrumentalizes civilian suffering not merely as a collateral effect, but as a primary mechanism of warfare to achieve military-political objectives. The paper posits that this constitutes a grave violation of the IHL prohibitions on starvation of civilians as a method of combat and the duty to ensure the basic needs of the population under occupation, as codified in the Geneva Conventions and Additional Protocols. Furthermore, it argues that the systematic degradation of civilian infrastructure essential for survival, including the health, water, and sanitation systems, through a combination of bombardment and blockade, creates an impossible environment for implementing core IHL rules. By blurring the line between permissible siege tactics and the illegal collective punishment of a civilian population, this strategy renders the principle of distinction operationally ineffectual, as it becomes impossible for civilians to “remain outside the conflict” when their very survival is made contingent upon military outcomes. The paper concludes that the Gaza siege paradigm signifies a profound crisis for IHL, demanding a reconceptualization of how the law regulates access and necessity in densely populated urban battlefields, and highlights the urgent need for robust, enforceable mechanisms to hold state and non-state actors accountable for using human survival as a strategic variable for war.